2013
DOI: 10.2134/jeq2013.02.0049
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Fouling of In Situ Ultraviolet-Visual Spectrometers Used to Continuously Monitor Water Quality in Brackish Tidal Marsh Waters

Abstract: The introduction of portable in situ ultraviolet-visual spectrometers has made possible the collection of water quality parameters at a high frequency in dynamic systems such as tidal marshes. The usefulness of this technology is inhibited by fouling of the instrument's optics. In this study, a spectrometer fitted with manufacturer-recommended compressed air optical cleaning was installed in a brackish marsh to determine if fouling interfered with measurements between bi-weekly servicing. During a 2-wk period,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…Observed differences in concentrations of TSS (p = 0.88), PO 4 -P (p = 0.24), and TP (p = 0.67) were not significant when the time between sample collection and a site visit was 13 days, suggesting that this is a reasonable time interval for analyses. All of the samples analyzed for DOC and nitrogen species (NH 4 -N, TKN, NO 3 -N) were collected within 24 hours before a site visit, because it was shown that these concentrations significantly changed (α = 0.1) over a 2-week period (Etheridge 2013). Within 24 hours of returning to the lab, samples that were analyzed for any of the dissolved species were filtered with Millipore Sterivex-GP 0.22 μm filters.…”
Section: Sampling and Analytical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Observed differences in concentrations of TSS (p = 0.88), PO 4 -P (p = 0.24), and TP (p = 0.67) were not significant when the time between sample collection and a site visit was 13 days, suggesting that this is a reasonable time interval for analyses. All of the samples analyzed for DOC and nitrogen species (NH 4 -N, TKN, NO 3 -N) were collected within 24 hours before a site visit, because it was shown that these concentrations significantly changed (α = 0.1) over a 2-week period (Etheridge 2013). Within 24 hours of returning to the lab, samples that were analyzed for any of the dissolved species were filtered with Millipore Sterivex-GP 0.22 μm filters.…”
Section: Sampling and Analytical Methodsmentioning
confidence: 99%
“…Despite the development and implementation of this system, some fouling still occurred on the instrument optics. More details about the severity of the fouling and the system developed to reduce fouling can be found in Etheridge et al (2013).…”
Section: Instrumentationmentioning
confidence: 99%
“…In this perspective, copper plates, tubing and shutters were proposed by Manov et al to delay biofouling [5]. Chlorination resulting from either bleach injection or electrolysis [6] or the use of pressurized fresh water cleaning [7] have also been reported as means of chemical cleaning of sensors' lens and housing.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have continued and extended the uncertainty line of research (Birgand et al 2010(Birgand et al , 2011(Birgand et al , 2013Moatar et al 2012;Williams et al 2015). Much of this research has focused on furthering scientific understanding of flow measurement uncertainty and the uncertainty in nutrient flux related to sampling frequency and load estimation technique.…”
Section: Mcmillan Et Al (2012) Highlighted the Duet-h/wq Tool And Damentioning
confidence: 95%
“…The abundant information embedded in absorbance spectra has been used to develop a more robust relationship to predict not only parameters known to absorb light (e.g., NO 3 , dissolved organic C, and total suspended solids) but others as well (e.g., phosphate [PO 4 ], organic N, bromine [Br], iron [Fe], and silicon [Si]) (Etheridge et al 2014;Birgand et al 2016). Even though all optical instruments (i.e., turbidity, absorbance, and fluorescence sensors) are subject to biological and chemical fouling (Etheridge et al 2013), these in situ sensors are potentially transformative because they can ideally provide high frequency data and avoid many of the constraints associated with field sampling and laboratory analysis.…”
Section: Current Research and A Glimpse Into The Futurementioning
confidence: 99%